Documentation of Medicinal Plants of Botanical Garden Haladkeri Sasyodyana of Bidar District, Karnataka, India - Rohit Jirobe; Dr.Venkat M Shinde (International Journal of Scientific Research in Science and Technology, 2025)
This study documents the medicinal plants of Sasyodyana, a botanical garden in Bidar District, Karnataka. A systematic survey was conducted to identify and classify plant species based on their medicinal properties. The study recorded a diverse range of species used in traditional medicine for ailments such as liver disorders, skin diseases, diabetes, respiratory conditions, and inflammatory disorders. The research also highlights the ethnobotanical significance of these plants and their role in biodiversity conservation. Findings emphasize the need for preserving indigenous knowledge and promoting sustainable utilization of medicinal plants for future pharmacological applications.
Keywords: Medicinal plants; Sasyodyana; Ethnobotany; Traditional medicine; Biodiversity conservation; Pharmacological applications; Plant documentation; Karnataka flora